The influence of social media in increasing public awareness of the importance of immunization - Ekayanti, Ekayanti (Innovative Approaches in Health Science Journal, 2024)
Background: Social media has become an important platform for disseminating health information, including immunization. However, misinformation is also easily spread, causing doubts about vaccination. This study aims to evaluate the role of social media in increasing public awareness of immunization, especially at the Bontobahari Health Center. Methods: This study used an analytical survey design with a cross-sectional approach. Data were collected in October 2024 from 25 mothers with toddlers in the Bontobahari Health Center area. Respondents were selected based on inclusion and exclusion criteria, and the data were analyzed using statistical tests to determine the relationship between social media use and immunization awareness. Results: Of the 25 respondents, 56% used social media, with 60% supporting immunization. The results of the statistical test showed a ρ value = 0.000, indicating a significant relationship between social media use and increasing public awareness of immunization. Platforms such as Facebook are the main source of information for most mothers. Conclusion: Social media has been shown to contribute positively to increasing public awareness of immunization. Effective use of social media, through education and involvement of community leaders, can expand immunization coverage. This study recommends that health workers use social media to disseminate accurate and interesting information.